Pengaruh Kompetensi Individu, Sikap Kerja dan Komunikasi Internal terhadap Kinerja Karyawan (Studi Kasus di PT Kido Mulia Indonesia) - Wihartiani Wihartiani; Slamet Bambang Riono; Indah Dewi Mulyani; Dumadi Dumadi; Akbar NP Darma Wahana (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of individual competence, work attitude, and internal communication on employee performance at PT Kido Mulia Indonesia. The background of this research is based on the importance of competent human resources, a positive work attitude, and effective internal communication in improving employee productivity. The research method used is quantitative with an associative approach. The sample consisted of 99 respondents who are employees of PT KMI, selected through purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The results show that, partially, the variable of individual competence has a positive and significant effect on employee performance, with a t-value greater than the t-table value and a significance level below 0.05. Similarly, work attitude and internal communication variables also have a positive and significant influence on employee performance. Simultaneously, the three independent variables significantly influence employee performance. The Adjusted R Square value of 0.736 indicates that 73.6% of the variation in employee performance can be explained by the three independent variables, while the remaining 26.4% is explained by other variables outside the model. The managerial implication of this research emphasizes the importance for company management to enhance employee competence through training programs, foster a positive work culture, and strengthen effective internal communication systems. These actions are expected to support the sustainable improvement of employee performance.